Evaluation of active slip systems during deformation by Insitu XRD in precipitation hardening Mg Alloys. Issue 1 (March 2021) - Yoshikawa, Tomoki; Hirata, Masahiro; Okai, Daisuke; Adachi, Hiroki
Abstract: The effect of precipitates on active slip systems was evaluated in precipitation-hardening Mg Alloys. In a Mg-5% Y-4% Nd (WE54) alloy, the radius and thickness of disc-shaped β" precipitates were measured by small angle X-ray scattering measurements. The active slip system was then measured during tensile deformation by in situ X-ray diffraction measurements. The average radius and thickness of the precipitates increased with aging time, and approached 19.4 and 3.85 nm, respectively, at a peak aging time of 2160 ks. The uniform elongations of the as-quenched, 1.08 ks aged and 36Q ks aged alloys were determined to be approximately 9.7, 5.5 and 2.3%, respectively. Various slip systems were active in the as-quenched alloy. On the other hand, in the alloy aged for 360 ks, non-basal slip was found to be dominant.